Comparison of Conventional and Ultrasound-assisted Femoral Nerve Motor Conduction Study in Healthy Controls - Abhinay Kumar Gattu; Y. Muralidhar Reddy; J.M.K. Murthy; ESS Kiran; Lalitha Pidaparthi; Shyam Krishnakumar Jaiswal; Anusha Pennuru; Ravi Nulaka; Sudhir Kumar (Journal of Medical Ultrasound)
Background: Ultrasound (US) can identify morphologic abnormalities and aid in the accurate localization of peripheral nerves. It can identify the femoral nerve and improve the stimulator placement in the femoral nerve motor conduction study. We aimed to compare the conventional and US-assisted femoral motor conduction techniques in a healthy population. Methods: One hundred and sixty-eight healthy controls (336 nerves) aged 18 years or more and both sexes were enrolled. Height, weight, body mass index (BMI), waist circumference (WC), and waist–hip ratio (WHR) were recorded. Stimulation of the femoral nerve was first done blindly (conventional) at the inguinal ligament and later at the site of the nerve identified using the US. Recording was done from the rectus femoris muscle. The mean and fifth percentiles of the compound muscle action potential (CMAP) obtained by both techniques were compared. Results: Mean (standard deviation) age of the cohort was 45.5 ± 14.01 years. US-assisted technique recorded larger CMAP than conventional in all age groups, gender, World Health Organization and Asia-Pacific BMI categories, WC, and WHR categories (P < 0.01). The fifth percentile of the CMAP amplitude was also higher in the US-assisted technique. Conclusion: Our results indicate that a US-assisted setup could improve conventional femoral nerve conduction studies.